Libélulas (Insecta) como indicadores da qualidade do habitat de riachos de lavrado em Roraima, Brasil - Pirela Pérez, Raúl Enrique (2018)
Human activities can cause great changes in the Landscape, affecting hydrological cycles and causing habitat degradation, which results in habitat homogenization. Bioindicator species can be used to assess change in ecosystems biological integrity, as they vary their composition and incidence on disturbed aquatic ecosystems. This study aims to evaluate the environmental integrity of Lavrado streams in Roraima using Odonates, in which we stipulated the following hypothesis: Odonata (Anisoptera and Zygoptera) richness and abundance are positively associated with the best rate of environmental stream quality because of their thermoregulatory capacity, their capacity of dispersal and habitat specialization. We sampled 10 Lavrado Streams in Roraima, Brazil, searching for the biggest variation across the savannahs of the region, in the months of October, November, and December of 2017, and March of 2018, the dry season. For each stream, we calculated the Habitat Integrity Index (HII), and we also determined adult Odonata richness, physicochemical variables, and the streamflow. In Lavrado areas there was no relation between the HII and Odonata richness. However, some species were nested in areas with intermediate values of integrity close to 0.5, and we believe that it is necessary to adapt the index, by including variables that can determinate the rate of disturbance of riparian savannah ecosystems. Zygoptera richness and stream’s environmental temperature were related negatively. This response in Zygoptera is explained by the fact that they are species with a low capacity of dispersal due to their small size, and therefore are specialists.